Expanding intestinal segment using osmotic hydrogel: An in vivo study. Issue 4 (12th October 2018) - Coletta, Riccardo; Olivieri, Claudio; Persano, Giorgio; Solari, Valeria; Inserra, Alessandro; Morabito, Antonino
Abstract: Intestinal circumferential expansion is essential for bowel lengthening in patients with Short Bowel Syndrome. We hypothesized use of an endoluminal osmotic hydrogel expander (EOHE) as a novel approach for intestinal expansion. An EOHE was introduced into an isolated intestinal segment of New Zealand rabbits, with a similar segment created as a control. After 4weeks, the segments were retrieved for analysis. Weight, inflammatory markers and fluoroscopy data was recorded weekly. EOHE allowed successful expansion of intestinal segments from 4.68 ± 0.35 to 9.79 ± 0.35 cm ( p = 0.01). Increase in intestinal length was 167.8 ± 35.21% in segments with EOHE vs. 23.03 ± 4.2% in the control group ( p < 0.01). A significant intestinal dilatation (214.4 ± 1.58 vs. 34.59 ± 1.23%, p < 0.01) was demonstrated. Hematoxylin and eosin stain revealed conservation of intestinal architecture with muscle hypertrophy and flattening of the epithelium possibly due to compression. No reduction of rabbit weight, inflammatory markers or liver damage was described. EOHE appears to produce safe intestinal expansion, achieving increased length and dilatation suitable for lengthening procedure. This approach may allow development of similar techniques to expand bowel in short bowel patients. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater 107B: 1304–1309, 2019.